The State of Shared Decision‐Making in Immune Thrombocytopenia: A Narrative Review and Health Care Provider Perspective - Shivi Jain; Kelsey Kuhel; Rose Cree; Michael D. Tarantino (Health Science Reports, 2026)
ABSTRACT Background and Aims Advances in the treatment of immune thrombocytopenia (ITP) have broadened the landscape of treatment options for patients. Shared decision‐making, a collaborative process between a patient and their health care team, is encouraged for these patients. The ultimate goal of shared decision‐making is to personalize treatment to achieve outcomes that are most important to the patient. However, there are no standard models for shared decision‐making in ITP. This narrative review provides a general overview of shared decision‐making, with a focus on ITP. Methods The PubMed database was searched for studies related to shared decision‐making in general, shared decision‐making in ITP, and shared decision‐making in hemophilia. Gray literature—including reports from professional and patient organizations focused on supporting patients with ITP and hemophilia—was also searched to capture a more comprehensive perspective. Results Select shared decision‐making models established in hemophilia, a bleeding disorder with both clinical and non‐clinical similarities to ITP, are discussed for their potential as guides for developing similar models in ITP. Patient characteristics and individual situations that can have an impact on the shared decision‐making process are detailed. Finally, we consider approaches to shared decision‐making in ITP with an emphasis on the experience of the authors as members of the Comprehensive Care team at the Comprehensive ITP Clinic at The Bleeding & Clotting Disorders Institute in Peoria, Illinois, which is the first Comprehensive Care Clinic for patients with ITP in the United States. Conclusion The development of shared decision‐making models specific to ITP may improve the consistency at which this approach is utilized. Shared decision‐making should be tailored to each individual patient's specific needs and treatment priorities/concerns. Utilization of ITP‐specific shared decision‐making models is expected to improve overall patient care and enhance the communication between patients and their healthcare providers.